2022
DOI: 10.1177/00220345221084975
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Stromal Cell Exosomes Ameliorate Periodontitis

Abstract: Human bone marrow stromal cell (hBMSC)–derived exosomes are promising therapeutics for inflammatory diseases due to their unique microRNA (miRNA) and protein cargos. Periodontal diseases often present with chronicity and corresponding exuberant inflammation, which leads to loss of tooth support. In this study, we explored whether hBMSC exosomes can affect periodontitis progression. hBMSC exosomes were isolated from cell culture medium through sequential ultracentrifugation. miRNAs and proteins that were enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Stem cell-derived exosomes provide a new cell-free treatment for periodontitis. hBMSC-derived exosomes suppressed the in ammatory responses of macrophages to P. gingivalis 18 and promoted periodontal regeneration 19 . In our in vivo study, we demonstrated that hBMSC-derived exosomes conditioned medium in promoting periodontal regeneration in a mouse model.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stem cell-derived exosomes provide a new cell-free treatment for periodontitis. hBMSC-derived exosomes suppressed the in ammatory responses of macrophages to P. gingivalis 18 and promoted periodontal regeneration 19 . In our in vivo study, we demonstrated that hBMSC-derived exosomes conditioned medium in promoting periodontal regeneration in a mouse model.…”
Section: Discussionmentioning
confidence: 97%
“…With a diameter of 30-200 nm, exosomes are considered as the delivery vehicle for bioactive compounds to target cells 17 . It has been reported that hBMSC-derived exosomes, rich in microRNAs (miRNAs) and proteins, can suppress the in ammatory responses of macrophages and promote periodontal regeneration 18,19 . miRNAs are small non-coding RNAs that modulate gene expression in various aspects of eukaryotic life, primarily via RNA-silencing mechanisms 20 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, PDLC/PDLSC-derived CEVs (PDLC/PDLSC-EVs) could inhibited cell pyroptosis and the production of inflammatory cytokines (IL-1β, IL-18 and TNF-α) in macrophages stimulated with LPS through NF-κB signaling pathway or delivering miR-590-3p silencing TLR4 and its downstream signaling pathway, to modulate the periodontal microenvironment [ 47 , 48 ]. CEVs derived from BMMSCs (BMMSC-EVs) was demonstrated to inhibit the inflammatory response of macrophages induced by Porphyromonas gingivalis ( P. gingivalis ), the keystone pathogen of periodontitis, and reduce the cell infiltration in rat periodontitis tissues [ 49 ]. Compared with BMMSC-EVs, gingival mesenchymal stem cell (GMSC)-derived CEVs (GMSC-EVs) promoted the expression of IL-10, Arg-1, CD206 and inhibit the expression of TNF-α in LPS-treated monocytes more effectively.…”
Section: Cevs and Periodontal Regenerationmentioning
confidence: 99%
“…Exosomes have been thought to be nature's endogenous nanoparticle delivery platform, and in particular, their miRNA cargo and growth factor are of significant interest (Swanson, Gong, et al, 2020 ; Swanson & Mishina, 2022 ; Swanson, Zhang, et al, 2020 ). Recently, human bone marrow stromal cell‐derived exosomes were demonstrated as a promising therapeutic in a preclinical rat periodontitis model to reduce tissue destruction and immune cell infiltration (Yue et al, 2022 ). The authors identified enrichment miRNAs associated with negative regulation of inflammatory response and increased protein abundance of factors including FGF‐6, insulin growth factor (IGF‐1), and interleukins: IL‐1ra, IL‐16, and IL‐3 concentrated in exosomes.…”
Section: Development Of Next‐generation Regenerative Therapeuticsmentioning
confidence: 99%
“…Chew et al demonstrated that mesenchymal stem cell‐derived exosomes, loaded in a collagen sponge, catalyzed periodontal regeneration in a rat model by activating pro‐survival AKT and ERK signaling (Chew et al, 2019 ). Yue et al similarly demonstrated that weekly exosome injections into gingival tissues suppressed pathogen‐triggered inflammatory responses by macrophages and showed their ability to be used as the most modulation agent in the management of periodontitis (Yue et al, 2022 ). Experiments studying the role of conditioned media and various secreted factors in the periodontium will undoubtedly lead to discoveries of bioactive molecules involved in physiologic tissue development, maintenance, and repair (Lin et al, 2021 ).…”
Section: Development Of Next‐generation Regenerative Therapeuticsmentioning
confidence: 99%